JK null alleles identified from Japanese individuals with Jk(a−b−) phenotype. Issue 4 (12th December 2013) - Onodera, T.; Sasaki, K.; Tsuneyama, H.; Isa, K.; Ogasawara, K.; Satake, M.; Tadokoro, K.; Uchikawa, M.
<x xml:space="preserve">Abstract</x> The Kidd blood group system consists of three common phenotypes: Jk(a+b−), Jk(a−b+) and Jk(a+b+), and one rare phenotype, Jk(a−b−). Jka/Jkb polymorphism is associated with c.838G>A (p.Asp280Asn) in exon 9 of the JK (SLC14A1) gene, and the corresponding alleles are named JK*01 and JK*02. The rare phenotype Jk(a−b−) was first found in a Filipina of Spanish and Chinese ancestry, and to date, several JK null alleles responsible for the Jk(a−b−) phenotype have been reported. We report seven novel JK null alleles, 4 with a JK*01 background and 3 with a JK*02 background, identified from Jk(a−b−) Japanese.